Improved rice variety (WITA 9) was adopted by 24% of rice farmers and increase income by US$ 91 per ha in Cote d'Ivoire - CGIAR Research Program on Rice (2019)
A household survey showed that the adoption rate was 24% among rice farmers. However, closer analysis showed adoption rates of 60% among those who had heard about WITA 9, and 71% among those who had access to it. The adoption of WITA 9 variety paddy yield advantage was 0.7 t ha–1, and its adoption increased farmer’s income by US$ 91 ha–1 per season.